News Media Partiality Concerning LGBT Issues in Indonesia: A Hidden Agenda of The Jakarta Post and Jakarta Globe - Meina Astria Utami (Ranah: Jurnal Kajian Bahasa, 2018)
This study is aimed at investigating the representation of LGBT in the Jakarta Post and Jakarta Globe and revealing hidden ideologies embedded in the representations. This study more specifically focuses on identifying how the two media deploy transitivity choices in reporting LGBT and gaining representational meanings from the transitivity choices. This study employs the qualitative method and transitivity analysis under the framework of Fairclough’s three-dimensional approach (1989). The study reveals that the Jakarta post tends to represent LGBT as a more passive participant in a way that certain circumstances shape them as a discriminated and intimidated group by several religious groups, society and government officials, therefore this position has caused Human Rights activists and several government officials to defend them. The media also depict LGBT as an acceptable identity and acknowledged phenomenon in Indonesia. On the other hand, Jakarta Globe tends to represent LGBT as a more active participant that they are given more space to express their sufferings and struggles that trigger them to claim their own rights through their active involvement in anti-LGBT discussions and the support provided by Human Rights activists. The findings suggest that the two media are struggling to promote democratic values in attempts to contribute to establishing LGBT acceptance in Indonesia (the Jakarta Post) and critiquing the discrimination as a means of ending intimidation against LGBT (Jakarta Globe). AbstrakPenelitian ini bertujuan untuk mendapatkan makna representasi dari pilihan transitivitas yang digunakan oleh laporan berita The Jakarta Post dan Jakarta Globe dalam mewartakan kasus LGBT dan mengungkapkanideologi yang mendasari representasi tersebut. Penelitian ini menggunakan metode kualitatif dan analisis transitivitas di bawah kerangka pendekatan tiga dimensi Fairclough (1989). Penelitian ini mengungkapkan bahwa The Jakarta Post cenderung merepresentasikan LGBT sebagai partisipan yang lebih pasif sehingga keadaan tertentu membentuk mereka sebagai kelompok yang terdiskriminasi dan terintimidasi oleh beberapa kelompok agama, masyarakat, dan pejabat pemerintah; dengan demikian, posisi ini menyebabkan aktivis HAM dan beberapa pejabat pemerintah membela mereka. Media juga menggambarkan LGBT sebagai identitas berterima dan fenomena yang diakui di Indonesia. Di sisi lain, Jakarta Globe cenderung merepresentasikan LGBT sebagai partisipan yang lebih aktif sehingga mereka diberikan ruang lebih untuk mengekspresikan penderitaan dan pergulatan mereka yang memicu mereka untuk mengklaim hak mereka melalui keterlibatan aktif dalam diskusi anti-LGBT dan dukungan yang diberikan oleh aktivis HAM. Hasil penelitian ini menyimpulkan bahwa kedua media berupaya mendorong nilai-nilai demokratis sebagai usaha untuk berkontribusi dalam menumbuhkan penerimaan terhadap LGBT di Indonesia (The Jakarta Post) dan mengkritik diskriminasi untuk menghentikan intimidasi terhadap LGBT (Jakarta Globe).